C96H30 tailored single-layer and single-crystalline graphene quantum dots. Issue 36 (26th August 2016) - Yuan, Biao; Sun, Xingming; Yan, Jun; Xie, Zheng; Chen, Ping; Zhou, Shuyun
Abstract : C96 H30 can be the precursor of single-layer and single-crystalline graphene quantum dots with a size-dependent effect. Abstract : By controllable synthesis of a carbon precursor and with a suitable preparation routine, a series of single-layer and single-crystalline graphene quantum dots (GQDs) with uniform size distribution were prepared from C96 H30 . It was found that the absorption, photoluminescence (PL) and two-photon photoluminescence (TPPL) show a high size-dependent effect with a redshift that occurs as the size grows. Two-photon absorption (TPA) properties of GQDs were measured at 800 nm under a femtosecond pulse laser. Two-photon bioimaging of HeLa cells was carried out to determine TPA properties. Most significantly, the as-prepared GQDs showed potential in a practical application in two-photon cell bioimaging due to their high contrast TPPL. In addition, the superior nonlinear absorption, stable TPPL and excellent solubility were beneficial to the optical limiting (OL) properties.